Guidance of gliding vehicles with energy management based on approximate prediction of speed - Cho, Namhoon; Kim, Youngil; Shin, Hyo-Sang; Kim, Youdan (Cranfield University, 2022)
This study presents a guidance method for flight vehicles gliding in the vertical plane to achieve desired position and velocity at the final time. The proposed guidance algorithm combines two decoupled elements to plan future flight trajectories satisfying the given constraints at each guidance update cycle: i) parametric path generator, and ii) approximate speed predictor. The parametric path generator is capable of producing an altitude profile as a parametric function of downrange by solving a convex optimisation problem considering only the shape properties of a flight path. An approximate method for predicting the future speed history endows the proposed guidance algorithm with the capability to address energy management objectives in trajectory planning. Provided that an altitude profile is specified by the parametric path generator and the lift-to-drag ratio model is known, the approximation neglecting gravitational acceleration turns the speed dynamics along the given path into a scalar linear first order ordinary differential equation, the form which admits a closed-form solution that can be represented by definite integrals. In this way, the proposed method opens a possibility to update the trajectory in flight to achieve the desired final speed by reducing the computational load due to speed prediction task, although the predicted speed contains approximation errors of certain degrees.
Keywords: Speed Prediction; Energy Management; Guidance; Glide Vehicles